Mixed pineapple jelly with pepper: preparation from pectin extracted from green apples and sensory, physicochemical, and microbiological characterization (Research, Society and Development, 2022)
Jelly is a word of French origin that means to solidify or gel. The product has a semi-transparent appearance and good consistency. For the preparation of the jelly, pineapple, pepper, pectin, sucrose, water and citric acid were used. Sensory characterization was performed by applying the Hedonic Acceptance Scale Test and the Attitude or Intention Scale Affective Test. The physicochemical parameters analyzed were pH, total titratable acidity, moisture and ash content and the microbiological analyzes determined Total Coliforms, molds and yeasts. The results of the sensory analysis indicated that 74.3% of the tasters liked it extremely and liked it moderately and 54.3% of the tasters would always eat and would eat often. In the physicochemical parameters, the jelly had a pH value of 3.8 and an average ATT content of 0.54%. In relation to the obtained moisture content (35.32%), this is in accordance with the Brazilian Legislation. Regarding the ash content obtained (4.11%), it should be noted that the current legislation for jellies does not mention the minimum ash content for the product. The result for Molds and Yeasts was